Pengaruh Tax Morale, Tax knowledge dan E-Tax System dengan Sanksi Pajak sebagai Variabel Moderating terhadap Kepatuhan Wajib Pajak Orang Pribadi - Dwi Nasihatul Lailiyah; Sri Andriani (Politeknik Ganesha Medan, 2023)
The purpose of this study is to assess and analyze the effect of tax morale, tax knowledge and e-tax system with tax sanctions as moderating variables on individual taxpayer compliance. The object of research is an individual taxpayer who is a member of the OPOP program in East Java. This study uses quantitative methods with primary data sources in the form of questionnaires containing respondent’s answers. Sampling technique using purposive sampling method. The Total population in this study was 550 individual taxpayers. The number of samples used in this study as many as 86 respondents using the formula slovin. Data analysis used in this study is a Structural Equation Model (SEM) based on Partial Least Square (PLS) using SmartPLS 4.0 software. Research Gap is the background of this study, which adds The Independent Variables tax knowledge, e-tax system, and tax sanctions as a variable moderation. The results in this study indicate that tax morale significantly affect the compliance of individual taxpayers in opop jatim. Tax knowledge has a significant effect on the compliance of individual taxpayers in opop jatim. E-tax system has a significant effect on the compliance of individual taxpayers in opop jatim. Tax sanctions as a moderating variable do not moderate the relationship between tax morale, tax knowledge and e-tax system to individual taxpayer compliance in opop jatim